(3EOGQI GdJShjbs - (3Ydj eMeO GdMGL(B, (3CMeOs; (3SejQ MSjf YhOI(B, s ((3YeGf(B:s (3ecJHI GdeLJeY(B,s, 2010)
(3Gdeaghe GdMOjK ddJShjb Hjf GdfXQjI h GdJWHjb , JfXje GdShb , GdJNWjW aj GdJShjb , fXe GdeYdheGJ GdJShjbjI h HMhK GdJShjb , eaghe GdGSJQGJjLjI GdJShjbjI , GSJQGJjLjGJ GdefJLGJ , ESJQGJjLjI efGaP GdJShjb , GJNGP GdbQGQGJ GdJShjbjI , JNWjW GdfTGW GdJShjbj , JfXje GdfTGW GdJShjbj (B.s
(3eQGLY U(B.239s
Keywords: (3COGQI GdeHjYGJs; (3GdJQhjLs; (3GdJShjbs